Imbrications or Constitutive Entanglements – A Matter of Ontologies - Marko Niemimaa (My University, 2022)
Scholars interested in theorizing sociomateriality debate whether social and material are discreet entities that interlock or constitutive entanglements. Prior theorizing suggests two philosophical world views underpin the debate: critical realism and agential realism. However, prior theorizing has not clearly articulated the philosophical assumptions and their relation to the debate or their influence on the used conceptions. In this research, I will relate imbrications to critical realism and constitutive entanglements to agential realism, and through juxtaposing the two expose some of the roots of the debate. The research suggests the debate can be largely explained in terms of ontological differences of each world view leading to misunderstandings and misappreciation of others' ideas. The research contributes to the debate on theorizing sociomateriality and to scholars interested in applying the world views to empirical research. This is a research in progress.
Proceedings of the ICIS 2014 SIGPHIL